INTENSITAS PENGGUNAAN MEDIA SOSIAL TIKTOK BAGI GENERASI ALPHA DI KECAMATAN CIBUNGBULANG - Noer Taufik , Rachmi Fidhara; Muslikhah , Febri Palupi; Nirwana , Testa Pradia (JURNAL SAHID DA'WATII, 2024)
This research aims to determine the intensity of use of TikTok social media among the Alpha generation, especially in Cibungbulang District. TikTok, which is a popular platform among teenagers, offers a variety of features that support interaction, entertainment and creativity. This research uses a quantitative approach with a descriptive design to describe the relationship between motives, duration and frequency of TikTok use by junior high school (SMP) students in Cibungbulang District. Data was collected through questionnaires distributed directly to 40 respondents using a purposive sampling technique, which was then analyzed using SPSS and the Pearson correlation test. The research results showed that the majority of students (57.5%) had a low level of intensity of using TikTok, followed by 22.5% of students with high intensity, 17.5% very low, and 2.5% very high. The use of TikTok is more dominant in the frequency indicator, which reaches 50%, followed by motives for use (25%) and duration (25%). This research confirms that the intensity of social media use, which is influenced by motive, duration and frequency, has a significant influence on the Alpha generation's habits of using TikTok as a means of entertainment, communication and social identity formation